Low Immunogenicity of Intravesical Phage Therapy for Urogenitary Tract Infections - Sławomir Letkiewicz; Marzanna Łusiak-Szelachowska; Ryszard Międzybrodzki; Maciej Żaczek; Beata Weber-Dąbrowska; Andrzej Górski (MDPI AG, 2021)
Patients with chronic urinary and urogenital multidrug resistant bacterial infections received phage therapy (PT) using intravesical or intravesical and intravaginal phage administration. A single course of PT did not induce significant serum antibody responses against administered phage. Whilst the second cycle of PT caused a significant increase in antibody levels, they nevertheless remained quite low. These data combined with good therapy results achieved in some patients suggest that this mode of PT may be an efficient means of therapy for urogenital infections and a reliable model for a clinical trial of PT.